2012
DOI: 10.1007/s12298-012-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water deficit stress on biochemical characteristics of safflower cultivars

Abstract: Water deficit stress is one of the severe limitations of crop growth especially in arid and semiarid regions of the world as it effect the plant growth at all stages of development. In the present study, four safflower genotypes Esfahan native, Esfahan-14, PI537,598 and IL111 were tested for their growth and crop yield under water-deficit stress. A detailed biochemical analysis was carried out at various levels of irrigation to find out the genotypic variation and the activity of several enzymes known to play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
(29 reference statements)
2
17
0
Order By: Relevance
“…The first two cultivars were characterized by higher proline content, which explained their tolerance to drought stress. Sajedi et al (2012) reported similar findings when they measured proline and two enzymes (P5C reductase and P5C synthetase) involved in the proline biosynthetic pathway when they screened two safflower varieties, one drought tolerant (cv. A1) and one sensitive (cv.…”
Section: Solute Accumulationmentioning
confidence: 53%
See 4 more Smart Citations
“…The first two cultivars were characterized by higher proline content, which explained their tolerance to drought stress. Sajedi et al (2012) reported similar findings when they measured proline and two enzymes (P5C reductase and P5C synthetase) involved in the proline biosynthetic pathway when they screened two safflower varieties, one drought tolerant (cv. A1) and one sensitive (cv.…”
Section: Solute Accumulationmentioning
confidence: 53%
“…It can also be produced in roots and later transported to shoots to regulate stomatal movements and leaf expansion. Sajedi et al (2012) reported a significant increase in the levels of ABA which in combination with increased antioxidant enzyme activity and proline content, improved the drought tolerance of four safflower genotypes. Although, drought stress and cultivar did not affect ABA content; however, under stressed conditions, intraspecific variation was observed among safflower cultivars.…”
Section: Phytohormonesmentioning
confidence: 91%
See 3 more Smart Citations